Concise Review: Aggressive Colorectal Cancer: Role of Epithelial Cell Adhesion Molecule in Cancer Stem Cells and Epithelial‐to‐Mesenchymal Transition. (17th April 2018) - Boesch, Maximilian; Spizzo, Gilbert; Seeber, Andreas
Abstract: Colorectal cancer (CRC) is one of the most common malignancies worldwide. In spite of various attempts to ameliorate outcome by escalating treatment, significant improvement is lacking particularly in the adjuvant setting. It has been proposed that cancer stem cells (CSCs) and the epithelial‐to‐mesenchymal transition (EMT) are at least partially responsible for therapy resistance in CRC. The epithelial cell adhesion molecule (EpCAM) was one of the first CSC antigens to be described. Furthermore, an EpCAM‐specific antibody (edrecolomab) has the merit of having launched the era of monoclonal antibody treatment in oncology in the 1990s. However, despite great initial enthusiasm, monoclonal antibody treatment has not proven successful in the adjuvant treatment of CRC patients. In the meantime, new insights into the function of EpCAM in CRC have emerged and new drugs targeting various epitopes have been developed. In this review article, we provide an update on the role of EpCAM in CSCs and EMT, and emphasize the potential predictive selection criteria for novel treatment strategies and refined clinical trial design.Stem Cells Translational Medicine 2018;7:495–501 Abstract : Conceptual framework for therapeutic targeting of EpCAM in malignant disease. Malignant tumors, including those of the colorectum, are characterized by marked heterogeneity and harbor phenotypically and functionally distinct subsets of cells. EpCAM‐targeted treatment of colorectal cancer is promising as it should affect many of these subsets including bulk tumor cells, CSCs, CTCs, and MET cells (only EMT cells lacking target expression will be spared). Expected outcomes are the containment (or even shrinkage) of the primary tumor as well as the inhibition of metastatic dissemination and recurrence. Traditionally, EpCAM‐directed treatments have focused on antibody‐based compounds targeting surface epitopes (i.e., EpEX). The recognition of nuclear translocation of EpICD as a potent oncogenic trigger now asks for complementary approaches involving membrane permeable drugs (i.e., small molecules). Abbreviations: CSC, cancer stem cell; CTC, circulating tumor cell; EMT, epithelial‐to‐mesenchymal transition; EpCAM, epithelial cell adhesion molecule; EpEX, EpCAM extracellular domain; EpICD, EpCAM intracellular domain; MET, mesenchymal‐to‐epithelial transition.